Pengaruh penambahan madu dengan dosis berbeda dalam media pengencer NaCl fisiologis terhadap kualitas sperma ikan tawes (Barbonymus gonionotus) - Oni Septiana Devi; Titik Susilowati; Ristiawan Agung Nugroho (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2019)
Silver barb (Barbonymus gonionotus) is one of the freshwater fish that is native in Indonesia. One of the problems in hatching of silver barb is because the maturation period of gamete broodstock male and female fish does not happen together. The solution to solving this problem is through the application of reproductive biotechnology in form of sperm storage. High sperm concentration can inhibit spermatozoa activity and affect sperm to find microphils. The addition of honey in dilute solution of physiological NaCl is expected to be able to improve the quality of sperm of silver barb. The aim this research was to know the effect and the best honey dosage in physiological NaCl on sperm quality of silver barb. The test fish that will be used in this research is 1 broodstock male and 1 broodstock female with 1-1,5 years old. In this research, the Completely Randomized Design experimental method is used. This research also using 4 treatments and 3 repetitions. Those treatment were A (0 ml honey + 100 ml physiological NaCl), B (0,2 ml honey + 99,8 ml physiological NaCl), C (0,4 ml honey + 99,6 ml physiological NaCl), D (0,6 ml honey + 99,4 ml physiological NaCl). The result of this research shows, addition of honey with different doses in dilute solution of physiological NaCl gave significant effect (p < 0,05) on fertilization rate and hatching rate of silver barb. The treatment D (0,6 ml honey + 99,4 ml physiological NaCl) gave the best on fertilization rate 90,67% and hatching rate 86,67%.